Bonefire of the vanities - Haines, Carolyn (New York : Minotaur Books, 2012)
Tracking down a porn star-turned-psychic who has promised to reunite an eccentric billionaire with her dead child, a suspicious Sarah Booth goes undercover as a maid at the billionaire's estate, where she discovers multiple murders and a host of suspects.
edited hb 2015-06-16
Keywords: Delaney, Sarah Booth (Fictitious character) -- Fiction; Women private investigators -- Mississippi -- Fiction; Mystery fiction